Thermophysical properties of masonry units: Accurate characterization by means of photothermal techniques and relationship to porosity and mineral composition. (15th February 2016) - Cobîrzan, N.; Balog, A.-A.; Belean, B.; Borodi, G.; Dădârlat, D.; Streza, M.
Highlights: Natural stones from exploitable quarries located in Transylvania has been analyzed. Thermophysical properties of masonry units were measured by photothermal techniques. An image processing procedure for measuring the porosity has been proposed. The mineralogical composition and porosity affect the thermo-physical properties. Limestone can offer an alternative solution for cladding the walls. Abstract: The concerns on saving energy and CO2 emissions in residential sector made the measures adopted in the last years to be focused on using building envelope materials with low embodied energy and improved thermo-technical properties. Considering that the sustainable behavior of materials during the buildings entire life cycle is much influenced by its mineralogical content, thermo-technical characteristics and physico-mechanical properties, the paper analyze from this point of view three types of masonry units (tuff, limestone, autoclaved aerated concrete) in order to be used as units in masonry works or for wall cladding. The mineralogical content has been determined microscopically in thin sections and by X-ray diffraction while the samples' porosity was measured into laboratory by volumetric methods and by using a new binary image analysis algorithm. Contact photopyroelectric calorimetry and non-contact infrared lock-in thermography have been used in order to measure with high accuracy the dynamic thermal parameters (thermal diffusivity, effusivity and conductivity) of these materials. The results highlights that mineralogical content, size and distribution of pores directly influence the thermal characteristic of materials and their behavior to moisture transport and decay process in aggressive environment.